Moderasi agama sebagai solusi masa kini terhadap pluralitas dan ekstremisme di Indonesia - Mardiana, Abdilah Reza; Paramitha, Attahiraa Prajna; Bhirawa, Bintang Surya (Maliki Interdisciplinary Journal, 2024)
Religious moderation is the main factor in creating harmony and tolerance. Rejecting extremism and liberalism in religion is the key to balancing moderation for the sake of creating peace. Religious moderation is understood as a perspective, attitude and behavior to always take a middle position, act fairly and not be extreme in religion. Indonesia is a country that is pluralistic and varied in terms of social, cultural and religious aspects. Conflicts between religious groups can certainly occur if a religious mindset emerges that only accepts truth and salvation one-sidedly. Therefore, there needs to be a solution from the Government, especially the Ministry of Religion, which has the responsibility to maintain inter-religious harmony. In fulfilling this responsibility, there needs to be cooperation between the government and various parties, such as religious leaders, academics and the general public. With a shared commitment from all parties involved, a more inclusive, peaceful and harmonious society can be achieved, where religious diversity is seen as a source of wealth and strength, not as a source of conflict.